The Benefits of Hybrid Modality to the Grade 11 HUMSS Students at Bestlink College of the Philippines: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The purpose of this study is to determine the benefits of hybrid modality to the Grade 11Humanities and Social Sciences (HUMSS) students at Bestlink College of the Philippines interms of their learning, communication, financial support, time management, adaptation ofhybrid systems, and resource availability.The survey's results, along with other study-related aspects, showed that using a hybridmodality boosted students' academic performance. A majority of survey respondents stronglyagree that applying a hybrid learning approach benefits them because it allows them to usetechnological advances as a learning tool with greater efficiency, increases their learning, andfosters accountability. When engaging in face-to-face classes in the hybrid modality, they caneasily communicate with their instructors and classmates. However, adjusting to the hybridmodality of learning enables students to learn in more effective ways. The majority ofrespondents who responded strongly agreed that using the LMS gives them better access toinformation and, therefore, helps improve their comprehension of their classes.This study recommended that the students ought to be encouraged to develop moreconfidence in participation and learn how to interact with or adjust to the system in a hybridmodality. It is further urged that the hybrid learning modality's grading system be improved inthe future so that students can utilize it as a driving force.
Keywords: Education